RELIGIOSITY EFFECT ON FERTILITY STUDY GROUP ON ISLAM - Radhiah, Sitti; Stang, Stang; Arsi, Andi Arsunan (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective :Modernizationis consideredby someto fail inmaintaining moral valuesandhumanity, causing increased tendency for people tobelieve inreligious values are considered able to providesolutions tovarious problems of life, so they are constantly adjusting options and decisions included indeterminings ome matters related to fertility.The aim of the research was to investigate the determinants ofwoman fertility of reproductive couples in Islamic study group in South Palu Distric of Palu City. Materialand Method : The reasearch was an observational study with cross sectional study design. The sampleswere the total population of the women of reproductive couples in Islamic study group of Soth Palu Districtconsisting of 149 people. The method of obtaining the data was interview and the data were analyzed usingpath analysis. Results: The research indicate that the variable affecting the age of the first marriage isemployment (p=0.004); the variables affecting contraception are knowledge (p=0.002) and religiosity(p=0.000); the variable affecting unmet need is religiosity (p=0.019); the variables affecting fertility areknowledge (p=0.014), employment (p=0.006), age of the first marriage (p=0.021), contraception (p=0.008),and unmet need (p=0.002), while income and breastfeeding duration do not significantly affectfertility.Conclusion : The effect on the fertility of the group is the study of Islamic knowledge, employment,age at first marriage, contraception and unmet need.